PEMAHAMAN PRINSIP TRANSPARANSI, AKUNTABILITAS DAN PENGENDALIAN INTERNAL DALAM PENGELOLAAN KEUANGANDI AISYIYAH CABANG KESAMBEN, BLITAR - Nathasya Aditya Wardiana; Sawitri Dwi Prastiti (Universitas Negeri Malang, 2016)
The aim of this study is to define the treasurer understanding regarding transparency principle, accountability, and internal control in financial management. The data is collected by conducting in depth interview for primary data and reviewing other related data. The results of this study show that (1) transparency principle of financial management in Aisyiyah at Kesamben Branch is shown in financial recording and reporting phase; (2) accountability principle of financial management in Aisyiyah at Kesamben Branch is reflected as intrinsic motivation in vertical and horizontal accountability; yet (3) Aisyiyah at Kesamben Branch has not carried out the function of internal control in financial management which is reflected from the existence of dual function in institution and school with no authority.Keywords: transparency, accountability, internal control, financial management